Back to basics : state power in a contemporary world - Finnemore, Martha; Goldstein, Judith (New York : Oxford University Press, 2013)
Edited by Martha Finnemore and Judith Goldstein, this book asks scholars to reflect on the role power plays in contemporary politics and how a power politics approach is influential today. The arguments made by the authors in the volume speak to one of three themes that run through Krasner's work: state power and hegemony; the relationship between states and markets; and conceptions of the nation state in international politics.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Power (Social sciences); International relations; World politics